Professional satisfaction of the members of the nursing team working at SAMU/Natal - Campos, Renata Moreira (2017)
Descriptive exploratory study, prospective and quantitative approach, performed in the Medical Regulation Central of SAMU/Natal, aiming to identify the level of professional satisfaction of the members from the nursing team working at SAMU/Natal; and verifying the degree of importance attributed by the professionals to each of the components of Professional Satisfaction: autonomy, interaction, professional “status”, work requirements, organizational rules and remuneration. The population was composed by 60 professionals, with data colleted from January to February from 2005. We used Professional PSR instrument to collect the data. The results demonstrated predominance of the female gender (54,9%); aged between 36 and 45 years old (60,8%); married (58,8%), 82,4% with children, 30,8% aged between 05 and 09; 78,4% were nursing technicians and 21,6% nurses, formed from 11 to 15 years (27,5%); 81,8% nurses have specialization, 29,4% of the team has been working from 11 to 15 years at the urgency area, 58.8% work for more than 02 years at SAMU, 72,6% of the team members have fixed work schedules; 41,2% during the day shift and 53% during the night shift. Regarding to the reason of to be working on SAMU, 84% chose to work in the service, and among these 76,3% perform direct care; 96,1% like and are satisfied to work in the service. Regarding the remuneration, 90, 9% of the nurses receive 05 to 10 minimum wages; 70% of the technicians receive -2 to 05 minimum wages. We indentified that the nursing team considered the Autonomy component as the most important. We identified that they were most satisfied with the Professional “Status and the real professional satisfaction level, calculated through statistics, however, these professionals are more satisfied with Autonomy. The PSR in our work was of 8,6, indicating that the nursing team has little satisfaction on their work environment.